Prevalence of Covishield COVID-19 Vaccine (ChAdOx1 nCoV-19) Adverse Effects among Health Care Workers in Sri Lanka. (March 2022) - Manilgama, S.R.; Hettiarachchi, N.M.; Jayasinghe, K.I.; De Silva, S.; Wanigaratne, T.; Jayalath, T.; Bandusiri, R.P.; Suganthan, N.; Sudarshan, P.; Pathirage, M.; Rajaratnam, N.; Senaratne, G.; et al.
Abstract : Purpose: A Community vaccination programme is the best approach to combat COVID-19 pandemic. The first priority was given to the health care workers (HCWs) with the introduction of Indian Covishield (ChAdOx1 nCoV-19) vaccine to Sri Lanka since February 2021. An independent post-vaccine surveillance is important to identify the occurrence of adverse effects(A/E) in the population. Methods & Materials: A multicentered cross-sectional survey was conducted in four provinces of Sri Lanka to estimate the prevalence of A/E after covishield vaccination A/E among HCWs after the first dose. A self-administered questionnaire was used to gather demographic data and A/E. Data was analysed using descriptive statistics. Results: Of 4834 participants, 3500(72.4%) were females. The median age was 42.23(SD±9.64) years. Only 0.8%(n=31) persons has had Covid infection in the past. 2.2% were breastfeeding mothers and 0.2% were pregnant ladies. 87.4% of persons had at least one A/E and 53.1% had local A/E. Body aches(68.2%), headaches(63.8%), fever(58%), chills 51.4%), fatigue(41.2%), arthralgia(38.1%) and rigors (32%) were the most commonly reported systemic A/E. Most of the systemic A/E were more prevalent among the ≤42-year-old group, and females. Their duration was mainly 24 hours. Mean duration of onset of fever is 9.76 hours. Pain and redness at the site were the most commonly reported local A/E. All of the local A/E were more prevalent among the ≤42-year-old group and females. Mean duration of pain at the site is 4.47 hours. 1.7%(n=61) had reactions within first 20 minutes. 0.08%(n=4) developed anaphylaxis, 0.8%(n=31) had urticaria. 15.4% had at least one comorbidities but there were no significant association between having a comorbidity and developing systemic or local. 1.3% had history of drug or food allergies, they did not show significant relation to current vaccine induced allergies or anaphylaxis. 69.2% attended the routine work despite having minor A/E. 0.13%(n=7) were hospitalised and treated. 22.4% were stayed at home and rested for 24-48 hours due to A/E. Conclusion: Eventhough more than 60% reported minor A/E, there were only a few serious A/E. A/E were more prevalent in younger age and females. Overall, the first dose of the Covishield vaccine was well-tolerated by HCWs.